Mitigação do desperdício de alimentos: práticas e causas na díade fornecedor-supermercado - Moraes, Camila Colombo de (2020)
Food waste is a matter of priority on international agendas, given its environmental, social and economic impacts. In this context, the implementation of practices to mitigate food waste is an efficient way to support economic growth and reduce social and environmental impacts. However, the literature is dominated by research carried out in developed countries and, although the practices presented are useful, there are few analyzes in developing countries, especially in Brazil. Reduction practices should be adapted to local situations of each country, in order to deal with the different barriers and facilitators for their implementation. Thus, the purpose of this research was to understand how external resources (RDT - Resource Dependence Theory) and internal resources (RBV - Resourced Based View) that influence the adoption of practices to mitigate the causes of FV (fruits and vegetables) waste in the supplier-supermarket dyad. First, a literature review was carried out, followed by a multi-case study composed of four cases (supplier-supermarket dyad), in which the activities of distribution, storage, exhibition, handling and disposal of FV in stores and distribution centers were analyzed. Thus, it was possible to characterize the external and internal resources to understand how they can influence the adoption of reduction practices, reflecting in the mitigation of the causes of FV waste. The resources identified in this research play a different role in each member of the dyad and can become barriers or facilitators for reducing food waste. Legislation, cultural aspects, financial aspects (financial return) and the lack of encouragement for cooperation can be barriers to the implementation of reduction practices. While access to technology, expansion of the relationship network, location, training and knowledge of operations can act as facilitators for this implementation. As a theoretical implication, this research identifies mitigation practices and causes of food waste, within the context of a developing country like Brazil. Second, it identifies an individualistic behavior in supermarkets, which, due to its great market power, pushes waste to other links in the supply chain. Third, it uses two theories within organizations to understand food waste in the context of the supply chain. As a managerial implication, the findings in this study can help managers to identify and map the causes of food waste in their operations, as well as to analyze the best reduction practices according to the particularities of each organization. Besides that, with the identification of barriers and facilitators, supermarkets and suppliers can adjust strategies to overcome these barriers, as well as analyze the opportunities arising from the facilitators, sharing benefits and costs.